Trypanosoma cruzi: behavior of metatrypomastigotes from didelphis marsupialis and panstrongylus geniculatus - Herrera, Leidi; Urdaneta Morales, Servio; Carrasco, Hernán (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Trypanosoma cruz; colonizes the anal scent glands of Didelphis marsupialis opossum, differentiating into metatryposmastigotes, which affect mammals through contamination in the same way as do metacyclics formed in the stomach of the triatomine vector. Meta-tryposmastigotes harvested from anal glands of D. marsupialis and from the intestine of Panstrongylus geniculatus, both of which naturally infected when captured in urban areas of the Caracas valley, Venezuela, were inoculated by the intra-peritonal (i.p.) route in NMRl mice for comparison of infectability, tissue tropism, and virulence. Metacyclic trypomastigotes from both sources produced 100% infectivity and mortality, causing heart, skeletal muscle, pancreas, colon, liver and lung invasion, however glandular metacyclic caused higher tissue parasite proliferation. Mice inoculated with glandular trypomastigotes showed, additionally, invasion of the smooth muscle of testis, epididymus, different conduct and seminal vesicles. Control opposums inoculated i.p. with glandular trypomastigotes, developed parasitemia and colonization of the anal glands. The latter in turn, i.p. inoculated in mice, induced lethal parasistemia. Results are discussed in relation to the extreme variability of T. cruzi populations which might correspond to different simultaneous cycles of transmission in particular ecotopes. The epidemiological importance of the presence of T. cruzi metacyclic stages in anal opossum glands in rural and urban areas is emphasized.